Mood-congruent recollection and anosognosia in Alzheimer's disease. (November 2016) - Bertrand, Elodie; Dourado, Marcia C.N.; Laks, Jerson; Morris, Robin G.; Landeira-Fernandez, Jesus; Mograbi, Daniel C.
Abstract: The aim of the study was to investigate experimentally the impact of current mood state on anosognosia or awareness of symptoms in AD patients, in which mood state was manipulated by giving tasks that were either easy (success condition) or very difficult (failure condition). Twenty-two patients with mild to moderate AD participated. Four success-failure manipulation (SFM) computerized tasks were used as mood induction procedures, two based on reaction time tasks and the other on memory tasks. Level of awareness and the current mood state were assessed before and after each task, using a modified version of the Anosognosia Questionnaire for Dementia and a self-reported questionnaire respectively. For both types of task, the results indicate that the emotional state of the participants was similar before performing the tasks and that only the failure conditions induced a negative mood state. Additionally, regarding the level of awareness, there were no significant differences after the reaction time tasks but for the memory tasks, there was greater awareness of symptoms after performing the task in the failure condition. To the best of our knowledge, this study is the first exploring experimentally the impact of mood on anosognosia in AD. The results showed an improvement of awareness of symptoms after negative mood induction, but only when the task used in the SFM was memory-based.